Missing in the Middle: A Review of Equatorially Disjunct Marine Taxa - Ludt, William B. (Frontiers in Marine Science, 2021)
Disjunct distributions of flora and fauna have intrigued biogeographers for centuries and have been central to debates over the roles that dispersal and vicariance have in speciation and evolutionary biology. One of the most notable disjunct distributions is when a single species or closely related taxa are present in temperate or polar regions of both hemispheres, but absent near the equator. Generally referred to as an anti-tropical distribution, this pattern is prevalent in marine taxa, occurring across the Tree of Life from single-celled bacteria and radiolarians, to algae, many invertebrates, fishes and marine mammals. The abundance of different species that exhibit this distribution pattern has led to a large number of theories on how it is formed and maintained. Here, seven central hypotheses that recur throughout the literature regarding the mechanisms responsible for this pattern are described and discussed in light of both historic and contemporary data. Recent advances in paleoclimate modeling and phylogenetic approaches have revealed that three of these hypotheses lack support. However, these data also highlight that a single driver of anti-tropicality is unlikely and that multiple mechanisms are responsible for this observed distribution pattern. The importance of using a multifaceted approach in future studies that incorporates phylogenetic, physiological, life history and ecological data is discussed, as there is a gap in our knowledge regarding adult and larval behavior, as well as thermal tolerances of many anti-tropical species. While recent studies have helped reveal some commonalities between anti-tropical groups, only by using an integrative approach will we be able to more fully understand which mechanisms are most prevalent in driving this pattern across the oceans.